2014
DOI: 10.1364/boe.5.001626
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating low cost and high performance elastomer lenses using hanging droplets

Abstract: Existing methods for low cost lenses using parallel mold stamping and high temperature reflow requires complex engineering controls to produce high quality lenses. These manufacturing techniques rely on expensive equipment. In this paper, we propose a low cost (< $ 0.01 per pc) flexible moldless lens fabrication method based on curing a hanging transparent polydimethylsiloxane (PDMS) elastomer droplet on a curved substrate. Additional deposition of hanging droplets in the same manner led to a substantial incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 16 publications
0
74
0
2
Order By: Relevance
“…12,14 A recently introduced method of creating PDMS lens by gravity-assisted hanging droplet formation has both the advantage of low cost and good optical quality; however, the process requires iterative drop-bake cycles to achieve the desired focal length. 15 In this paper, we describe a method to fabricate lenses by inkjet printing of PDMS droplets on a heated surface. The small PDMS droplet is released at a prescribed height from the inkjet print head.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 A recently introduced method of creating PDMS lens by gravity-assisted hanging droplet formation has both the advantage of low cost and good optical quality; however, the process requires iterative drop-bake cycles to achieve the desired focal length. 15 In this paper, we describe a method to fabricate lenses by inkjet printing of PDMS droplets on a heated surface. The small PDMS droplet is released at a prescribed height from the inkjet print head.…”
Section: Introductionmentioning
confidence: 99%
“…The trapping lens of our optical manipulation system was formed from hanging droplets of PDMS, which had been prepared using the typical so lithography PDMS procedure, and followed similar steps as those outlined by Lee et al, 7 and shown in Fig. 1(a)-(c).…”
Section: Fabricating the Trapping Lens With A Hanging Dropletmentioning
confidence: 99%
“…The particle size was chosen as previous studies 7 have shown the smallest resolvable structure with droplet lenses to be 4 mm. Fig.…”
Section: Optical Manipulation Using a Drip Lensmentioning
confidence: 99%
“…The drive to develop technology capable of analysing the outputs from such devices has led to innovations in the area of image processing and analysis on mobile phones [7], along with new low cost, or low-tech, imaging techniques [8][9][10][11] making use of, for example, holographic microscopy. Other areas that have benefited from leveraging consumer technology and simple home-made techniques include miniature dermascopes [12], centrifuges made from egg beaters [13], not to mention the huge potential of 3D printing in such areas, spanning chemical reactionware [14] to conventional printing of chips [15].…”
Section: Introductionmentioning
confidence: 99%
“…Elastomeric optics have been used in an increasing number of novel applications such as a rubber microscope [18] and biologically inspired wide field lenses [19]. Additionally, lenses based on hanging droplets of PDMS have been fabricated and used in a low-cost digital dermascope [12] and low-cost optical traps [20].…”
Section: Introductionmentioning
confidence: 99%